Quality of Life and Associated Risk Factors in Caregivers of Patients with Obsessive Compulsive Disorder. Issue 4 (2nd October 2019) - Sücüllüoğlu Dikici, Didem; Eser, Erhan; Çökmüş, Fikret Poyraz; Demet, Mehmet Murat
ABSTRACT: INTRODUCTION: Obsessive compulsive disorder (OCD) is a chronic disease that affects social relationships, and occupational and academic performance of patients and their relatives due to cognitive, emotional, and behavioural aspects of the disease. Quality of life (QoL) in relatives of patients with OCD has previously been reported and compared with caregivers of patients with other psychiatric conditions. However, there are few studies available in the literature regarding the causality of QoL in caregivers of patients with OCD. OBJECTIVE: The aim of this study was to evaluate QoL of caregivers of patients with OCD and predictors of QoL of the family caregivers. METHODS: The study population comprised of 68 patients with OCD and their caregivers. The dependent variable of this study is "QoL of caregivers" as assessed by the short version of the World Health Organization Quality of Life questionnaire (WHOQOL-BREF-TR). The Structured Clinical Interview for DSM-IV/Clinical Version (SCID-I/CV), Yale-Brown obsessive-compulsive scale (Y-BOCS), Y-BOCS symptom checklist, Hamilton Depression Rating Scale (HAM-D), and WHOQOL-BREF-TR were completed by the patients, whereas the SCID-I/CV, WHOQOL-BREF-TR, and Burden Assessment Scale (BAS) were completed by the caregivers. Student's t -test, MWU, ANOVA, Kruskal–Wallis ANOVA, and Spearman's correlations were used in univariate analyses, and multiple linear regression tests were run in multivariate analyses. Critical VIF values were taken as 5.0 for detecting collinearity among independent variables in the regression analyses. Type 1 error was taken as 0.05 in the analyses. RESULTS: Linear regression analysis showed that caregivers' sex, education level, occupational status, disease burden, and patients' sex, physical QoL, and disease severity were predictors of caregivers' QoL. Moreover, disease burden was the only common predictor that affected all four dimensions (physical, psychological, social relations, environmental) of the caregiver's QoL, and as the perceived disease burden increased, the caregiver's QoL deteriorated.